Novel alginate/polyethyleneimine hydrogel adsorbent for cascaded removal and utilization of Cu2+ and Pb2+ ions. (15th February 2019) - Godiya, Chirag B.; Liang, Ma; Sayed, Sayed Mir; Li, Dawei; Lu, Xiaolin
Abstract: Heavy metal ion pollution leads to severe health risk to human beings. Herein, a natural and highly efficient sodium alginate (ALG)/polyethyleneimine (PEI) composite hydrogel was designed and fabricated for the removal of heavy metal ions from wastewater. The adsorption of heavy metal ions on the ALG based, 3D composite hydrogel were thoroughly investigated in this study. Furthermore, the in situ reduced metal nanoparticle-loaded ALG/PEI composite hydrogel provided us a sustainable utilization route of the heavy metal ion with a promising adsorption-catalysis ability. In general, this research will present an effective and practical paradigm for the cascaded treatment and recycling of heavy metal ions in wastewater. Graphical abstract: Image 1 Highlights: Novel ALG/PEI hydrogel was prepared for the removal of heavy metal ions. Excellent adsorption property for the Cu 2+ and Pb 2+ ions was characterized. The adsorbed Cu 2+ ions were in situ reduced to form a Cu NPs-loaded hydrogel. The Cu 2+ NPs-loaded hydrogel proved to be an excellent catalyst for the reduction of 4-NP.